FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK BAGI WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA MALANG UTARA - Apriliana Apriliana; Nur Hidayati; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTTax is an alternative source of potential state income, the right choice, and a stable amount, as well as a form of community contribution in the country's development. Indonesia is a large country, but state revenues from taxes are still low due to lack of awareness of people who have fulfilled the requirements of the object and the tax subject to pay taxes. The purpose of this study is to find out the factors that influence the compliance of paying taxes for taxpayers, these factors are: knowledge, understanding, and awareness of taxpayers, as well as service tax authorities. This type of research is a quantitative approach using questionnaire spread. The population in this study is a taxpayer at the Tax Office Pratama Malang Utara. While the sample in this study is the taxpayer who reports the Annual Notice until July 2019. There is a partial effect of variable knowledge, understanding, and awareness of taxpayers on compliance with paying taxes, while service tax authorities do not have a partial influence on compliance with paying taxes at KPP Pratama Malang Utara.Keywords: compliance with paying taxes, knowledge of taxpayers, understanding of taxpayers, and awareness of taxpayers, as well as service of tax authorities